Design of Teaching Materials to Criticize Information from Various Sources in Grade XII of High School Based on Language Motives in Cybercrime Actions - Ariyanto, Zahy Riswahyudha; Rahmawati, Laili Etika (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The urgency of this research is the urgent need to accelerate digital literacy education for the younger generation as a preventive effort to deal with cybercrime. Currently, cybercrime is wrapped in complex persuasive, and manipulative language. Methodology: This research is development research that adopts the Three-D (3-D) model, a modification of the Four-D model, which consists of three stages: Define, Design, and Develop. The focus of this research is to develop Indonesian language teaching materials for grade XII SMA Merdeka Curriculum students to critique information from various sources based on language motives in cybercrime actions. At the Define stage, researchers define the characteristics of persuasive language in cybercrime and their relevance to Indonesian lan-guage learning in high school. The Design stage includes data classification and categorization to design a learning design that focuses on language mo-tives in digital communication that intends to deceive. At the development stage, teaching materials are refined and compiled based on the results of the analysis, accompanied by the preparation of a learning flow. Research data comes from literature reviews and electronic documents, including articles, journals, and digital texts, such as doxing, scamming, and phishing. The data collection techniques used are document study and content analysis, while the data analysis technique applies framework analysis with the stages of da-ta reduction, coding, presentation, and interpretation. Data validity is main-tained through triangulation of sources and methods. Results: The results of this study are the results of the development of teaching mate-rials and stages of learning to criticize information from various sources. Applications/Originality/Value: In conclusion, the development of this teaching material is a preventive ef-fort to deal with cybercrime and supports the development of digital literacy and 21st-century learning based on 4C.